Assessment of the Contamination by 14C Airborne Releases in the Vicinity of the Ignalina Nuclear Power Plant. Issue 5 (October 2019) - Pabedinskas, Algirdas; Maceika, Evaldas; Šapolaitė, Justina; Ežerinskis, Žilvinas; Juodis, Laurynas; Butkus, Laurynas; Bučinskas, Laurynas; Remeikis, Vidmantas
ABSTRACT: A radiocarbon ( 14 C) activity analysis in the tree rings around Ignalina nuclear power plant (INPP) has been carried out with the aim to test the hypothesis to use 14 C tree-ring analysis data as a tool for the reconstruction of gaseous releases from NPP to the environment. The INPP has been in decommissioning state since the end of 2009. Tree-ring samples for 14 C analysis were collected 7 yr after final power unit shutdown from the INPP vicinity. The samples from 5 sampling locations were collected, prepared and measured using the Single Stage Accelerator Mass Spectrometer (SSAMS). Data analysis represents observable Ignalina NPP influence by 14 C increase up to 15 pMC (percent modern carbon) in tree rings. Good correlations of the 14 C concentrations and wind direction were obtained. The main purpose of this article was to match 14 C measurement data along with the atmospheric dispersion modeling of emissions in order to retrospectively characterize the emission source.